Heavy Metal Accumulation Resulting from Petroleum Waste Disposal in Terrestrial Ecosystems: A Case Study in Dry and Desert Ecosystems of Southern Libya - Nouraldin Almahdi Ibrahim Basha (Journal of Scientific and Human Dimensions, 2026)
The disposal of petroleum waste in oil-producing areas creates serious environmental hazards for desert ecosystems because their soil restoration process moves at an extremely slow pace. This research study examines heavy metal pollution which exists in the soils that surround the Sharara and Elephant Al-Fil and NC-186 Mutakhendush oil fields found in southern Libya. Researcher used pollution indices together with simulated datasets which environmental assessments produced to assess pollution levels of Cd and Cr and Cu and Pb and Zn and Ni and V in locations where produced water and drilling wastes and accidental spills occurred. The results show that metal levels have increased beyond natural background levels while pollution indices show moderate to high contamination in multiple sampling sites. The spatial analysis reveals how different operational activities and waste disposal methods create distinct operational patterns. The research examines bioremediation methods together with AI-powered geographical mapping systems which will improve monitoring efficiency and help develop remediation strategies. The results demonstrate that Libya must create more effective petroleum waste management techniques in order to reduce ecological harm and protect significant desert habitats in southern Libya.